2019
DOI: 10.3390/nu11112811
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association between Breastfeeding and Dental Caries among Three-Year-Old Australian Aboriginal Children?

Abstract: An unresolved question about breastfeeding is its effect on caries, in particular, early childhood caries (ECC). In secondary analyses of data from an ECC intervention, we describe breastfeeding among Aboriginal children and associations between breastfeeding and ECC. Breastfeeding (duration and exclusivity to six months) was grouped into mutually exclusive categories. ECC was observed by a calibrated dental professional. Outcomes were prevalence of ECC (% decayed, missing, and filled teeth in the primary dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 15 publications
1
17
0
1
Order By: Relevance
“…It was observed in this study that ECC was associated with prolonged night-time breastfeeding. This is similar to what was reported in an Australian study by Haag et al [26]. In the study, they observed an association between exclusive breastfeeding for six months and continued breastfeeding for 24 months with 1.45 higher caries prevalence.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It was observed in this study that ECC was associated with prolonged night-time breastfeeding. This is similar to what was reported in an Australian study by Haag et al [26]. In the study, they observed an association between exclusive breastfeeding for six months and continued breastfeeding for 24 months with 1.45 higher caries prevalence.…”
Section: Discussionsupporting
confidence: 92%
“…Breastfeeding has many well-established benefits for both mother and baby, thus, potential effects of breastfeeding on caries should be mitigated by improving oral hygiene and access to oral healthcare [26].…”
Section: Discussionmentioning
confidence: 99%
“… 32 Haag and others described how breast feeding >24 months was associated with higher dental caries prevalence at child age 3 years compared with children who were never breast fed. 33 This is contrary to the many findings that support prolonged breast feeding among Indigenous Australians for better child health outcomes. Santiago and colleagues demonstrated how social support was characterised among study participants, 34 and the impact of personal control on self-reported health outcomes.…”
Section: Findings To Datementioning
confidence: 87%
“…Some studies reported that breast feeding is associated with higher rates of p ECC while other studies found no association [11,12]. On the other hand, a lot of studies found higher prevalence of ECC among children who were bottle fed when compared with those who were exclusively breast fed [13,14].…”
Section: Discussionmentioning
confidence: 99%